2019
DOI: 10.18632/aging.101758
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA-ES3/miR-34c-5p/BMF axis is involved in regulating high-glucose-induced calcification/senescence of VSMCs

Abstract: Vascular calcification/aging is common in diabetes and is associated with increased morbidity and mortality of patients. MiR-34c-5p, not miR-34c-3p, was suppressed significantly in calcification/senescence of human aorta vascular smooth muscle cells (HA-VSMCs) induced by high glucose, which was proven by the formation of mineralized nodules and staining of senescence associated-β-galactosidase staining (SA β-gal) positive cells. Overexpression of miR-34c-5p alleviated calcification/senescence of HA-VSMCs, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 39 publications
4
50
0
Order By: Relevance
“…Renal replacement therapy including hemodialysis, peritoneal dialysis, and renal transplantation are the main treatments for patients with ESRD [2]. Vascular medial calci cation is mainly contributed to calcium and phosphate deposition [5,18]. In this study, there was no signi cant difference in blood lipid among patients with ESRD, RTR, and the healthy control.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Renal replacement therapy including hemodialysis, peritoneal dialysis, and renal transplantation are the main treatments for patients with ESRD [2]. Vascular medial calci cation is mainly contributed to calcium and phosphate deposition [5,18]. In this study, there was no signi cant difference in blood lipid among patients with ESRD, RTR, and the healthy control.…”
Section: Discussionmentioning
confidence: 51%
“…Vascular calci cation is mainly characterized as the medial of aortic calci cation (termed as Mönckeberg's calci cation), and it often happens in patients with chronic kidney disease, especially end stage renal disease (ESRD) [1,2]. Lots of studies have demonstrated that vascular calci cation is not a simple passive process of calcium and phosphorus deposition but an active regulatory process, and the transdifferentiation of vascular smooth muscle cells (VSMCs) into osteoblast-like cells is regarded to be the key pathophysiological factor of vascular calci cation [3][4][5]. However, the speci c mechanism of vascular calci cation in patients with ESRD is still not entirely elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…11 In previous work, we demonstrated that calcification/senescence of VSMCs is regulated by the lncRNA-ES3/miR-34c-5p/BMF axis. 12 However, that study did not elucidate the specific role of lncRNA-ES3 in calcification/senescence of VSMCs, and the overall mechanism remained largely uncharacterized.…”
Section: Introductionmentioning
confidence: 98%
“…For example, lncRNA-ES3 can regulate calci cation/senescence of vascular smooth muscle cells through an miR-34c-5p/BMF axis that is activated upon HG induction. [38] The lncRNA SENCR shows high abundance of expression in vascular cells, [37,39,40] and can regulate fork-head box protein O1 and transient receptor potential cation channel 6, thereby promoting the proliferation and migration of smooth muscle cells. HG exposure of T2DM db/db mice can inhibit the expression and function in smooth muscle cells, and overexpression of SENCR reverses the inhibitory effect of HG on vascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%